2020
DOI: 10.1080/13573322.2020.1825934
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative systematic review of critical pedagogy in Physical Education and Sport for Development: exploring a dialogical and critical future for Sport for Development pedagogy

Abstract: This is the first systematic qualitative review to examine and organise the current body of research that addresses the practical application of critical pedagogy within Physical Education and Sport for Development. Following a rigorous systematic review process, this paper analyses critical pedagogy, social justice and social transformation through Freire's (1972) concept of dialogical and anti-dialogical action. The themes generated through the analysis of Physical Education were (1) the challenge of teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…For SFD, that means developing practices, funding and networks that actively seek to challenge and reshape social structures while moving away from reproduction of existing power relations through individual, life-skill focused programming. In many ways, the seeds of such an approach exist in what is variously termed structural or interventionist approaches (Hartmann and Kwauk, 2011;Sabbe et al, 2021), as well as within ideas of critical pedagogy (Meir, 2022). What is crucial here, however, is that we need not only to rethink how we deliver programmes on the ground, but how we actually build and structure the organisations delivering those programmes.…”
Section: Escaping Capture?mentioning
confidence: 99%
“…For SFD, that means developing practices, funding and networks that actively seek to challenge and reshape social structures while moving away from reproduction of existing power relations through individual, life-skill focused programming. In many ways, the seeds of such an approach exist in what is variously termed structural or interventionist approaches (Hartmann and Kwauk, 2011;Sabbe et al, 2021), as well as within ideas of critical pedagogy (Meir, 2022). What is crucial here, however, is that we need not only to rethink how we deliver programmes on the ground, but how we actually build and structure the organisations delivering those programmes.…”
Section: Escaping Capture?mentioning
confidence: 99%
“…As a result, if coaches make even minor changes towards developing a more robust critical praxis, it may help them create more inclusive and welcoming spaces for youth athletes, where all participants can experience positive developmental outcomes (Kochanek & Erickson, 2019). Meir (2020) conducted a qualitative systematic review of critical pedagogy in physical education and sport for development, with findings suggesting that social transformation outcomes are more likely to take place when shifts in curriculum and professional development occur within broader organizational cultures of social justice. Taken together, these findings point to the need for coaches to adopt critical pedagogies across various youth sport programs (e.g., high school sport, sport for development), while being supported by coach professional development opportunities.…”
Section: Critical Consciousness In Sportmentioning
confidence: 99%
“…Beyond the privilege that led to Stephen's lack of social justice action, another reason that might have contributed to his reluctance and reactivity was the social climate in which he worked, which aligns with findings from Martin et al (2022) who suggested that senior college athletes were less likely to engage in social justice activism due to perceived lack of support. Moreover, a review from Meir (2020) suggested that shifts in curriculum and professional development related to social justice are more likely to be successful when they occur within broader organizational cultures of social justice. Although Stephen appeared satisfied with the promotion of social justice at his school, more data would need to be collected on the school environment in order to draw further conclusions.…”
Section: Reactivity and Reluctancementioning
confidence: 99%
“…Sport for Development and Peace (SDP) is a symbolic value of sport and physical education harnessed to promote social and human development in different spheres (Chawansky & Holmes, 2015) and, more specifically, in education globally (see e.g., Meir, 2020). In the context of the global expansion of SDP interventions that have occurred in recent years, the Global South, particularly sub-Saharan Africa, has been the largest target for organizations implementing these programmes.…”
Section: North-south Nexus In Sport For Development and Peacementioning
confidence: 99%